Oral Cancer Educational Materials for the General Public: - Vicki Chung, BS; Alice M. Horowitz, PhD; Maria T. Canto, DDS, MPH; Piya Siriphant, DDS, MPH (Blackwell Synergy, 2000)
Previous studies have shown that US adults are not well informed about oral cancers andonly 15percent everhave hadan oralcancer examination. This study sought to determine the quantity and adequacy of educational materials designed to inform or educate US adults about risks for, and signs and symptoms of, oral cancer and the need for an oral cancer examination